The lemonade war - Davies, Jacqueline, 1962- (Davies, Jacqueline, 1962- Lemonade war series ;, 2007)
Evan and his younger sister, Jessie, react very differently to the news that they will be in the same class for fourth grade and as the end of summer approaches, they battle it out through lemonade stands, each trying to be the first to earn 100 dollars. Includes mathematical calculations and tips for running a successful lemonade stand.